Sistem Seleksi Penerimaan Siswa Baru Menggunakan Metode Weighted Product - Bella Mayhendra; Petrus Sokibi (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2017)
The Acceptance of new students in SMA Negeri 1 Rajagaluh is done by choosing alternate prospective students who qualify based on predetermined variables. The problem faced by the team of selectors is how to determine the best students from a number of prospective students who have advantages and disadvantages of each with a very fast time so often mistakes in the selection of new students in SMA Negeri 1 Rajagaluh and less objective in providing an assessment for selected. In this thesis built a new decision support selection system using the method of Weighted Product (WP). The variables used in the selection of admissions in SMA Negeri 1 Rajagaluh are the national final examination scores, the final examination score of the school, the value of junior high school report cards. This system is designed using PHP programming language (Hypertext Processor File) as well as MySQL database as a database server. This system generates rankings of prospective new students in accordance with the procedure of admission of students in SMA Negeri 1 Rajagaluh, where the result is in the form of student ranking. This system has several advantages that variable and a weight value of variables used in this system is dynamic. This system also has a shortage of the range of values on the variable is still static